PROSES PEMBELAJARAN MENULIS PUISI BERDASARKAN KURIKULUM 2013 PADA SISWA SMAN 1 SUNGAI RAYA - Oktavianti, Andini Riski; Syambasril, Syambasril; Muzammil, Ahmad RabiÃºl (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research is motivated by the desire to know the process of learning to write poetry, and find out whether the teacher has implemented poetry writing learning based on the signs in the 2013 Curriculum. The method used in this research is descriptive method. Descriptive method in question is to describe the planning, implementation, and learning outcomes of writing poetry carried out by the teacher in the class X IPA SMA Negeri 1 Sungai Raya. The data of this study are the results of observations of the lesson plans made by the teacher, the results of observations on the implementation of learning, and the learning outcomes obtained by students. Sources of data in this study Indonesian Language students and teachers SMA Negeri 1 Sungai Raya. The results of the analysis show that the learning planning (RPP) formulated by the teacher in learning to write poetry has reflected the 2013 curriculum based learning. The implementation of learning that has been done by the teacher is in accordance with the 2013 curriculum. and skills assessment results. The results of the assessment are for the attitude value of class X IPA 1 to IPA 5 the overall average has shown good categories, for the results of the value of knowledge X IPA 5 the overall average score is 78 (Enough), IPA 2 78.86 (Enough ), IPA 4 81.48 (Good), IPA 3 81.46 (Good), and IPA 1 83.06 (Good). Furthermore, the results of the value of poetry writing skills have shown a fairly good category and only the class X IPA 5 of science has not reached the KKM on average. The average overall score for the skill grades of grade class X IPA 5 is 74.64, IPA 2 75.03, IPA 4 76.36, IPA 3 75.37, and IPA 1 75.90.Â Keywords: Learning Process, Writing Poetry, 2013 Curriculum